2021
DOI: 10.1002/vetr.450
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trimming, hoof angle and shoeing on breakover duration in sound horses examined with hoof‐mounted inertial sensors

Abstract: Objective: Aim of the current in vivo, observational study was to investigate the effect of trimming, heel elevation and different types of shoeing on breakover duration (BreakD) with a novel, hoof‐mounted inertial measurement unit (IMU) sensor system. Methods: Ten sound, crossbred horses were examined barefoot before and after trimming fitted with an IMU sensor at the dorsal hoof wall. Additionally, application of 5° heel wedges, plain steel shoes, rolled‐toe shoes and palmarly‐placed quarter‐clip shoes was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
4
3
0
1
Order By: Relevance
“…The reduction in breakover duration observed with increasing gallop speed is consistent with observations in walk and trot, which highlight breakover duration to be a primarily speed-dependent variable [30]. Our data additionally highlight an interesting distinction between breakover duration in hindlimbs and forelimbs, which is dependent on gallop speed.…”
Section: A 41 the Role Of Speedsupporting
confidence: 89%
See 1 more Smart Citation
“…The reduction in breakover duration observed with increasing gallop speed is consistent with observations in walk and trot, which highlight breakover duration to be a primarily speed-dependent variable [30]. Our data additionally highlight an interesting distinction between breakover duration in hindlimbs and forelimbs, which is dependent on gallop speed.…”
Section: A 41 the Role Of Speedsupporting
confidence: 89%
“…Given the variability between the front and hind limb data, these results support the notion that breakover in fore and hind limbs should be evaluated separately [30,37]. However, this study additionally found important differences arose between the individual limbs in response to shoeing condition (see section 4.3), suggesting a limb-by-limb approach is most appropriate for interpreting data from this asymmetric gait.…”
Section: A 41 the Role Of Speedsupporting
confidence: 75%
“…The reduction in breakover duration observed with increasing gallop speed is consistent with observations in walk and trot, which highlight breakover duration to be a primarily speed-dependent variable [29]. Our data additionally highlight an interesting distinction between breakover duration in hindlimbs and forelimbs, which is dependent on gallop speed.…”
Section: The Role Of Speedsupporting
confidence: 89%
“…Given the variability between the forelimb and hindlimb data, these results support the notion that breakover in forelimbs and hindlimbs should be evaluated separately [13,29]. However, this study additionally found important differences arose between the individual limbs in response to shoeing condition (see Section 4.3), suggesting a limb-by-limb approach is most appropriate for interpreting data from this asymmetric gait.…”
Section: The Role Of Speedsupporting
confidence: 74%
“…The influence of shoeing on horse upper body motion has also been reported, including the effect lateral hindlimb road nails and orthotic lifts have on increasing pelvic motion in trotting horses [76,77]. The nature of the hoof trim can also be influential to gait kinematics, including breakover duration [78][79][80][81], although this finding is not universal [82]. However, data collected from horses used in other equestrian disciplines and at slower gaits are not directly relatable to the racehorse.…”
Section: Introductionmentioning
confidence: 99%